Sow reproductive disorders: a key issue affecting the pig industry - Wang, Yihan; Jin, Youshun; Wang, Yanyan; Li, Yunhui; Wang, Xiaoxue; Li, Zhaocai; Zhou, Jizhang (Frontiers in Veterinary Science, 2025)
Pig farming is essential to global agricultural economies and food security. However, reproductive disorders in sows significantly impact the economic viability and sustainability of the pig industry. These disorders often result from complex interactions between pathogenic and non-pathogenic factors. Preventing abortions is typically more cost-effective than managing and treating them, particularly in intensive pig farming system. This highlights the importance of comprehensively understanding the underlying causes of abortion in sows. This review explores the factors contributing to sow reproductive disorders, including both non-infectious factors (environmental conditions and management practices) and infectious factors (viruses, bacteria, and parasites). We also outline preventive and control strategies, alongside integrated management approaches, by analyzing the underlying causes and pathogenic mechanisms of pregnancy disorders. Overall, implementing the “One Health” concept in large-scale farming provides an effective strategy to reduce the incidence of sow abortion rate, ensure stable livestock production, and maintain a reliable global pork supply.